(untitled) - Kahane, Howard (Belmont, California, 1995)
This text is designed for those instructors who desire a comprehensive introduction to formal logic that is both rigorous and accessible to students encountering the subject for the first time. Numerous, carefully crafted exercise sets accompanied by clear, crisp exposition give students a firm grasp of basic concepts and take the student from sentential logic through first-order predicate logic, the theory of descriptions, and identity. As the title suggests, this is a book devoted not merely to logic; students will encounter an extraordinary amount of philosophy as well. Upon completing the first two parts of the text, a student will be well prepared for advanced courses in analytic philosophy. The last part deals with supplemental matters-informal fallacies, modal logic, and inductive logic, among others.
Keywords: Logic